Surface reconstruction of defective SrTi0.7Cu0.2Mo0.1O3-δ perovskite oxide induced by in-situ copper nanoparticle exsolution for high-performance direct CO2 electrolysis. Issue 8 (July 2023) - Yang, Xiaoxia; Sun, Kening; Sun, Wang; Ma, Minjian; Ren, Rongzheng; Qiao, Jinshuo; Wang, Zhenhua; Zhen, Shuying; Xu, Chunming
Abstract: Solid oxide electrolysis cell (SOEC) provides an effective solution to electrochemically convert CO2 into valuable products with high efficiency, which is also developed as a promising way for the electricity utilization. However, the poor catalytic activity of the electrode material results in slow cathode kinetics for this technology. In this work, we propose a series of Sr x Ti0.7 Cu0.2 Mo0.1 O3-δ (S x TCM, x = 1, 0.975, 0.95) perovskite oxides as the cathodes of SOEC. By tuning the defects of the materials, abundant oxygen vacancies are stimulated in the perovskite lattice, which effectively improves the oxygen ion transport capacity and also act as the receptors of CO2 molecule. Uniformly dispersed Cu nanoparticles on STCM substrate are in-situ generated after reduction treatment, leading to the formation of abundant active sites for CO2 reduction reaction (CO2 RR). The results of this work demonstrate a general strategy for developing promising catalysts for efficient CO2 RR.